A novel ACVR1 mutation in the glycine/serine-rich domain found in the most benign case of a fibrodysplasia ossificans progressiva variant reported to date. - Gregson, C; Hollingworth, P; Williams, M; Petrie, K; Bullock, A; Brown, M; Tobias, J; Triffitt, J (2011)
Fibrodysplasia Ossificans Progressiva (FOP) is a rare, autosomal dominant condition, classically characterised by heterotopic ossification beginning in childhood and congenital great toe malformations; occurring in response to a c.617 G > A ACVR1 mutation in the functionally important glycine/serine-rich domain of exon 6. Here we describe a novel c.587 T > C mutation in the glycine/serine-rich domain of ACVR1, associated with delayed onset of heterotopic ossification and an exceptionally mild clinical course. Absence of great toe malformations, the presence of early ossification of the cervical spine facets joints, plus mild bilateral camptodactyly of the 5th fingers, together with a novel ACVR1 mutation, are consistent with the 'FOP-variant' syndrome. The c.587 T > C mutation replaces a conserved leucine with proline at residue 196. Modelling of the mutant protein reveals a steric clash with the kinase domain that will weaken interactions with FKBP12 and induce exposure of the glycine/serine-rich repeat. The mutant receptor is predicted to be hypersensitive to ligand stimulation rather than being constitutively active, consistent with the mild clinical phenotype. This case extends our understanding of the 'FOP-variant' syndrome.